Fumonisins and zearalenone fed at low levels can persist several days in the liver of turkeys and broiler chickens after exposure to the contaminated diet was stopped. (February 2021) - Tardieu, D.; Travel, A.; Le Bourhis, C.; Metayer, J.-P.; Mika, A.; Cleva, D.; Boissieu, C.; Guerre, P.
Abstract: Previous studies using zearalenone (ZEN) and fumonisins (FB) revealed alpha-zearalanol (α-ZOL) and FB1 in the liver of turkeys and chickens with no sign of toxicity. The aim of the present study was to determine whether contamination persists after distribution of a mycotoxin-free diet for several days. Turkeys and broilers were fed for 14 days with a diet containing respectively, 7.5 and 0.6 mg/kg of FB and ZEN, then fed for 0, 2 or 4 days with a mycotoxin-free diet. FB1 and total α-ZOL were the most abundant metabolites found, and their concentration decreased with time. The decrease was linear for FB1 (P < 0.001) and exponential for α-ZOL. Mean concentrations of FB1 on days 0, 2, and 4 were respectively, 4.9, 4, and 2.9 ng/g in turkeys, and respectively, 5, 2.3, and 1.3 ng/g in chickens. The decrease in concentration of FB1 with time was modeled by linear regression (P < 0.001). Mean concentrations of α-ZOL on days 0, 2 and 4, were respectively, 4.8, 0.8, and 0.5 ng/g in turkeys, whereas α-ZOL was only quantified in chickens on day 0 at 0.3 ng/g. A strong correlation was found between α-ZOL and β-zearalenol (P < 0.001). Highlights: Exposure to fumonisins and zearalenone is of great concern in humans and animals. The elimination kinetics of fumonisin B1 and α-zearalenol were measured in the liver. The study was conducted on chickens and turkeys at realistic exposure levels. Half-elimination times vary according to toxins and species, from a few hours to several days. The distribution of a mycotoxin-free diet should be long to avoid residues.